DEVELOPMENT OF PORTFOLIO INVESTMENT OF AN OIL AND GAS ENTERPRISE USING MULTI-FACTOR MODELING - R. Khasnutdinova; Y. Rudneva (Вестник Северо-Кавказского федерального университета)
The article proposes a methodology for forming an investment portfolio for a conservative type of investors using multifactorial models that allow predicting the value of financial instruments included in the portfolio. The primary goal was to select the financial assets that form the future investment portfolio based on the assessment of risk and return criteria. The following indicators were used as criteria when choosing the most effective investment portfolio: coefficient of variation, Sharpe coefficient, growth rate of the inancial instrument value.